AN ANALYSIS OF SARCASM IN MARVEL’S MOVIE “VENOM” - Laela Putriana Melawati (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2022)
Sarcasm can be a part of one’s speaking style that it may come out unintentionally out of habit when that person is speaking. Sarcasm can change a whole serious conversation into a laugh worthy one without losing its function, to mock or insult the addressee. Sarcasm can enrich the vibes of a movie where it is put into for example in Marvel’s Movie ““Venom””. This research is conducted to analyze what types of sarcasm used in the movie as well as the utterance’s context and how the addressee respond the sarcastic utterance. The theory and approaches that the researcher used are Pragmatic, and Camp’s theory of sarcasm types. qualitative method is applied in this study. The researcher uses several techniques such as watching, reading, identifying, classifying and selecting. While for analyzing data, the researcher displaying, explaining and interpreting method. The results of the study shows that Marvel’s “Venom” movie indeed contains several sarcasm remarks. Context is a crucial thing to define an utterance as sarcasm or not, as well as to define what an utterance’s actual meaning. Addressee’s response can be a support proof for an utterance to be called as sarcastic remarks.